2015
DOI: 10.1093/femspd/ftv006
|View full text |Cite
|
Sign up to set email alerts
|

Role of uropathogenic Escherichia coli outer membrane protein T in pathogenesis of urinary tract infection

Abstract: OmpT is one of the members of the outer membrane protein family that has been identified as a virulence factor in most of the uropathogenic Escherichia coli (UPEC). However, the exact role of OmpT in the urinary tract infections (UTIs) remains unclear. To determine the role of OmpT in the pathogenesis of UPEC, an isogenic deletion mutant of ompT (COTD) was constructed by the λ Red recombination. Human bladder epithelial cell line 5637(HBEC 5637) was used to evaluate the ability of bacterial adhesion/invasion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
0
26
0
1
Order By: Relevance
“…Detection of specific genes, including ompT , is often used to characterize virulent clinical UPEC isolates (Johnson et al, ; Najafi et al, ). Previous studies have suggested that OmpT from the UPEC strain CFT073 is involved in adhesion, invasion, and/or inactivation of AMPs (Brannon et al, ; He et al, ). While the presence of ompT is associated with virulent strains, its precise contribution remains unclear, as UPEC clinical isolates have highly variable genetic sequences (Schreiber et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of specific genes, including ompT , is often used to characterize virulent clinical UPEC isolates (Johnson et al, ; Najafi et al, ). Previous studies have suggested that OmpT from the UPEC strain CFT073 is involved in adhesion, invasion, and/or inactivation of AMPs (Brannon et al, ; He et al, ). While the presence of ompT is associated with virulent strains, its precise contribution remains unclear, as UPEC clinical isolates have highly variable genetic sequences (Schreiber et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In mouse urinary tract infection (UTI) models, following adhesion and internalization within bladder umbrella epithelial cells, UPEC can escape the endocytic vesicle and proliferate in the cytoplasm as intracellular bacterial communities (IBCs; Anderson et al, 2003). The presence of IBCs has been corroborated by numerous laboratories using a variety of mouse strains and UPEC isolates (Garofalo et al, 2007;He et al, 2015;Nicholson, Watts, & Hunstad, 2009;Wieser, Guggenberger, Pritsch, Heesemann, & Schubert, 2011). Isolation of IBCs from human UTI patients further establishes the physiological relevance of this intracellular growth phase (Rosen, Hooton, Stamm, Humphrey, & Hultgren, 2007;Scott, Haake, Churchill, Justice, & Kim, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…The latter include Afa/Dr adhesins, E. coli common pili, Fml pili, flagella, Outer membrane protein T (OmpT), the salmochelin siderophore receptor IroN, and the Rho GTPase-activating toxin Cytotoxic Necrotizing Factor 1 (CNF1) (see Fig. 4A) (101111). The specific sets of bacterial and host factors that are engaged by UPEC to gain access to intracellular niches likely vary as the pathogens encounter changing environments and host cell types during the course of a UTI.…”
Section: Mechanisms Of Bladder Cell Invasion By Upecmentioning
confidence: 99%